Phenology of arboreal plant species in a fragment of caatinga in Santana do Ipanema, AL, Brazil / Fenologia de espécies vegetais arbóreas em um fragmento de caatinga em Santana do Ipanema, AL, Brasil - Wandklebson Silva da Paz; Jefferson Thiago Souza (Universidade Estadual de Alagoas, 2018)
The phenology can be defined as the evaluation of periodic events of the life of a plant, and these events can be vegetative and reproductive and their interaction with biotic and abiotic factors. In this way, the objective of this work was to describe the period and the synchronism of the phenophases of arboreal plant species. Thus, this phenological study was conducted in the Private Equity Reserve Stakeout in Santana de Ipanema, Alagoas, where monthly observations of five tree species were made. It was taken into account the following phenophases: budding, leaf fall, flowering and fruiting. It used two methods of phenological evaluation (intensity index and sync rate). Thus, it was found high intensity index for budding and leaf fall, but also presented with high synchrony, and these phenophases are antagonistic, as they are dependent on water availability. Regarding reproductive phenophases, the dies showed constant throughout the study, with low intensity and asynchronous due to the low number of fruits produced by them.